The Relationship Between Self-Compassion and Blood Pressure Control Behaviour in Patients with Hypertension - Br Munthe, Cristina Lasmaria; Aziz, Ari Rahmat; Nopriadi, Nopriadi (Jurnal Keperawatan Profesional, 2025)
Blood pressure control behavior by hypertensive patients is driven by various factors, one of which is an attitude that encourages positive behavior. Self-compassion is an attitude of compassion for oneself towards problems and diseases suffered by caring, understanding and giving kindness to oneself. Objective: This study aims to determine the relationship between self-compassion and blood pressure control behavior in hypertensive. Methods: This research is a quantitative research with descriptive correlation design and cross sectional approach. The instruments used for data collection in this study were self-compassion scale questionnaire and blood pressure control behavior questionnaire. The research sample was 144 respondents selected by purposive sampling technique. The analysis used was the chi-square test. Results: The results of bivariate analysis using chi-square obtained the results of p-value (0.001) < alpha (0.05). Conclusion: There is a significant relationship between self-compassion and blood pressure control behavior in hypertensive patients at Rejosari Health Center Pekanbaru. The correlation obtained is positive, meaning that the higher the self-compassion, the better the blood pressure control behavior and vice versa, the lower the self-compassion, the less good the blood pressure control behavior.